A gender critique of the EU directive on platform work from the perspective of feminised and racialised labour - Nelli Kambouri (Labour & Law Issues)
The Directive on improving working conditions in platform work challenges deeply entrenched inequalities in platform work by regulating some aspects of the labour process that remain unregulated in most EU Member States. The Directive is the outcome of labour struggles and court cases that have taken place during the past years against the misclassification of platform workers as independent self-employed contractors and the non-transparent usage of algorithms in human resources management. Nevertheless, the Directive is gender blind and obscures intersectional aspects of algorithmic management. In the text of the directive there are few references to “gender” or to “women” and important issues like work-life balance, equal pay for equal work, sexual harassment, intersectional gender discrimination, or paid maternity and paternity leaves are mentioned but not considered. Based on the relevant literature, the article explores the gendered challenges that will emerge from its implementation especially regarding reproductive labour and algorithmic biases. More specifically the analysis uses existing research on intersectional gender inequalities from different areas of platform work, mostly crowdwork and domestic and care work, to explore how it will impact on the platform economy. The paper concludes by arguing that the fact that the Directive obscures the specific forms that gender inequality takes in platforms will further exasperate intersectional gender inequalities and discrimination in platform work